Rancang Bangun Aplikasi Pencarian Toko Servis Resmi Komputer Di Kota Pekanbaru - Dwi Asril Syaifudidin; Novi Yona Sidratul Munti; Hanantatur Adeswastoto (Jurnal Inovasi Teknik Informatika, 2021)
The role of information technology is never separated in all aspects of people's daily lives. One of the technological developments that affect data recording at this time is the Global Positioning System (GPS). The Global Positioning System (GPS) is a satellite-based navigation system that provides information about the location on the earth's surface easily, quickly, cheaply, and the accuracy can be justified. Especially in the development of spatial information or better known as Geographic Information Systems. Utilization of geographic information systems in the field of technology, namely being able to find the location of official computer service stores in Pekanbaru City. An authorized computer service shop is a trusted place for repairing various computer equipment. Because the technicians in this shop have special experience in each of their skills. In general, people feel doubtful and afraid when they want to repair computers at service shops that do not necessarily have special skills. With this Geographic Information System, it can make it easier for users of official computer service store services. These conveniences include finding the location of an authorized computer service shop, with the technicians having special skills according to the user's wishes or finding the location of the nearest authorized computer service shop from the user's point location.